(untitled) (CIPEEX, 2025)
Mobility and balance are motor skills developed especially in childhood and during early schooling. Encouraging activities that promote body control is essential to prevent delays in motor development that can affect adult life. This study evaluated the effects of virtual reality training and functional training on the mobility and balance of schoolchildren. The sample included 60 students from a public school, divided into three groups: control (CG), functional training (FTG), and virtual reality (VRG). Before and after the interventions, participants were assessed with the Timed Up and Go test (TUGi), using the G-Walk-BTS inertial sensor to measure mobility and balance. The results showed that the GRV group presented a significant improvement in the total duration of the TUG test in the post-training assessment compared to the pre-training assessment and the control group in the post-training assessment (8.91 ± 1.33 p <0.0001). The GTF group also showed a significant improvement in the total duration of the TUG test in the post-training assessment compared to the control group (8.31 ± 1.14 p<0.0001). In addition, the functional group obtained significant results in the duration of the walk and return in the post-training assessment compared to the control group (1.93 ± 0.56 and 1.67 ± 0.29 p < 0.0001). It is concluded that both virtual reality training and functional training are effective in improving mobility and balance in schoolchildren.